Photocatalysis and Photoelectrochemical Properties of Tungsten Trioxide Nanostructured Films - Chin Wei Lai (The Scientific World Journal)
Tungsten trioxide (WO3) possesses a small band gap energy of 2.4–2.8 eV and is responsive to both ultraviolet and visible light irradiation including strong absorption of the solar spectrum and stable physicochemical properties. Thus, controlled growth of one-dimensional (1D) WO3 nanotubular structures with desired length, diameter, and wall thickness has gained significant interest. In the present study, 1D WO3 nanotubes were successfully synthesized via electrochemical anodization of tungsten (W) foil in an electrolyte composed of 1 M of sodium sulphate (Na2SO4) and ammonium fluoride (NH4F). The influence of NH4F content on the formation mechanism of anodic WO3 nanotubular structure was investigated in detail. An optimization of fluoride ions played a critical role in controlling the chemical dissolution reaction in the interface of W/WO3. Based on the results obtained, a minimum of 0.7 wt% of NH4F content was required for completing transformation from W foil to WO3 nanotubular structure with an average diameter of 85 nm and length of 250 nm within 15 min of anodization time. In this case, high aspect ratio of WO3 nanotubular structure is preferred because larger active surface area will be provided for better photocatalytic and photoelectrochemical (PEC) reactions.